Desarrollo humano sustentable: concepto y naturaleza (2006)
The concept of Human Development Sustainable implies a conjunction of economic, legal, philosophical and anthropological elements that difficult a synthetic concept. That problem is made complex still more at the time of determining if it is a concept of legal nature that can be catalogued like a Human Right, or if it is only a political pretension. Nevertheless, the doctrinal development on the subject augur the existence of a right, at least in the nternational common law, on the economic development directed to the promotion of the human and social capacities, founded on the respect by environment and whit a vocation of generational progress.